Impossible - Steel, Danielle (New York : Delacorte Press, 2005)
Brought together by their mutual interest in art, Sasha, a widowed art gallery owner with grown children, and Liam, a successful artist nine years her junior, find new meaning in their lives through their relationship with each other.
Keywords: Artists -- Fiction; Love stories